Rencana dan Implementasi Manajemen Risiko Berbasis HSE dalam Proyek Seismik Migas di PT XYZ - Firman Amir; Ahmad Adrian Hanafiyah; Fariz Rochman Maulana; Nursaidah Nursaidah; Abdullah Maulana Ahsan (Jurnal Inovasi Global, 2025)
The oil and gas industry, particularly during the exploration stage such as seismic projects, faces high risks related to occupational safety and environmental impact. This study aims to identify and evaluate risk management strategies based on Health, Safety, and Environment (HSE) in a seismic oil and gas project at PT XYZ. Employing a descriptive qualitative approach, data were collected through field observations, in-depth interviews with key stakeholders, and analysis of HSE documents such as HIRARC and incident reports. The research was conducted across PALI, Muara Enim, and Musi Banyuasin Regencies in South Sumatra. The findings reveal that the primary risks include workplace accidents, social disturbances due to land conflict, and environmental pollution. Key implementation barriers of the HSE Plan include weak supervision in remote areas, uneven safety training, and the lack of a digital incident reporting system. Nevertheless, mitigation strategies such as work rotation schedules, emergency drills, and the involvement of local community leaders have proven effective in reducing risk exposure. This study highlights the importance of an adaptive HSE approach that considers geographic and social contexts and the need to digitize risk monitoring systems. The implications suggest that the risk management model developed from this research can serve as a practical reference for planning HSE strategies in other oil and gas exploration projects in Indonesia.